Negative reversal prints of thin sections: photographic technique and its significance - Haneef, Mohammad (Journal of Himalayan Earth Sciences, 1993)
Thin section photographs are one of the popular methods of data presentation in scientific research. In sedimentology, where greater details of sedimentary structures, textures and fossils are sometimes required, the field of view of the petrographic microscope is not large enough to cover the desired area of the thin section for photograph. The negative reversal print of a thin section, on the other hand, can provide a print of all or selected part(s) of the thin section with considerable details. The black and white photo print obtained using this technique has a better contrast and it can be used to draw line-drawings to further elaborate particular areas of interest.